Heuristics to Navigate Uncertainties: Interview With Professor Kathleen M. Eisenhardt. (July 2019) - Bodner, Julia; Song, Seo Yeon (Jamie); Szulanski, Gabriel
Kathleen Eisenhardt made numerous theoretical and methodological contributions to the fields of entrepreneurship, organization theory, and strategy. This interview focuses on her perspectives on how organizations in high-velocity environments can navigate technological uncertainties in fast-paced markets. In addition to clarifying her research contributions, she provides rare insight into her own academic development, her belief in teaching and mentoring, and her stance on intriguing issues future research should address.